2018
DOI: 10.2478/mape-2018-0076
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Innovations in Agricultural Production as a Pro-Development Factor of the Economy

Abstract: The study presents the impact of eco-innovation and policy conducive to the implementation of the principles of sustainable development in agriculture on economic development. The starting point was the analysis of economic growth models and indicating in them the approach to innovation for the implementation of sustainable development. The specifics of eco-innovation in the agricultural sector and their typology have been presented. Due to the complexity of innovative processes and in particular the resulting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…The authors in [ 14 ] used the established model to explain the relationship between the intergenerational income mobility of different countries and their intragenerational income inequality and found that in general, countries with high intergenerational income mobility have their income inequality. This would be lower; if two countries have the same intergenerational income mobility but different levels of income inequality, it is likely due to differences in the genetic process of their endowments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors in [ 14 ] used the established model to explain the relationship between the intergenerational income mobility of different countries and their intragenerational income inequality and found that in general, countries with high intergenerational income mobility have their income inequality. This would be lower; if two countries have the same intergenerational income mobility but different levels of income inequality, it is likely due to differences in the genetic process of their endowments.…”
Section: Introductionmentioning
confidence: 99%
“…e reduction of intergenerational income mobility can easily make China fall into the "middle income trap," so the government should take measures, such as the government's investment should be transferred from physical capital investment to human capital investment such as education and health, and not only the total amount should be increased, but also they should focus on eliminating inequalities in education and health to gradually transform social structures and increase intergenerational income mobility to avoid entering the "middle income trap." e authors in [14] used the established model to explain the relationship between the intergenerational income mobility of different countries and their intragenerational income inequality and found that in general, countries with high intergenerational income mobility have their income inequality. is would be lower; if two countries have the same intergenerational income mobility but different levels of income inequality, it is likely due to differences in the genetic process of their endowments.…”
Section: Introductionmentioning
confidence: 99%
“…The conflict of goals between them creates a dilemma in understanding the positioning of cooperatives [ 18 ]. Literature [ 19 ] builds a systematic theoretical analysis framework for the evolution of cooperative service functions by summarizing and condensing existing relevant theories, in order to get rid of the current apparent cognition of cooperative service functions and explore economic phenomena and organizations from a deeper theoretical level behavior.…”
Section: Related Workmentioning
confidence: 99%
“…The study in [ 19 ] believed that agricultural insurance is conducive to stabilizing the national economy and social life at the macrolevel; at the microlevel, it can compensate farmers' losses, stabilize the source of funds for farmers, and enhance farmers' ability to repay loans. In turn, the economic level will also affect agricultural insurance.…”
Section: Related Workmentioning
confidence: 99%